2008
DOI: 10.1097/inf.0b013e3181861dd7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Prepandemic Influenza A (H5N1) Vaccine in Children

Abstract: We confirmed our earlier findings of the present vaccine in adults showing encouraging safety and immunogenicity properties in children. Studies with the present vaccine in elderly subjects are underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…Our findings agree with those of a previous trial of the present vaccine, which found it to be immunogenic after a single dose of 6 g in 146 adults (24). We are now extending these studies to children, as a trial with a 6-g dose of the present vaccine in pediatric subjects was recently completed (26). Also, studies of cross-reactive immunity in a subset of the present study population were recently published (9).…”
Section: Discussionsupporting
confidence: 81%
“…Our findings agree with those of a previous trial of the present vaccine, which found it to be immunogenic after a single dose of 6 g in 146 adults (24). We are now extending these studies to children, as a trial with a 6-g dose of the present vaccine in pediatric subjects was recently completed (26). Also, studies of cross-reactive immunity in a subset of the present study population were recently published (9).…”
Section: Discussionsupporting
confidence: 81%
“…The reduced-dose vaccine (Fluval K, an inactivated, wholevirion, trivalent vaccine with 6 g of HA/strain/0.5 ml content and aluminum phosphate gel adjuvant; lot no. FL-K-004) was produced by Omninvest Ltd. (Budapest, Hungary) as described previously (8,(14)(15)(16)(17)(18)(19). With the exception of the antigen amount, the vaccine was prepared by the same method as for the licensed seasonal influenza vaccine Fluval AB (19) and the licensed prepandemic vaccine Fluval H5N1 and the licensed pandemic H1N1 vaccine Fluval P (8,(14)(15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%
“…Typical trivalent seasonal influenza vaccines are unadjuvanted split-virion or subunit vaccines and contain 15 g of hemagglutinin (HA) per virus strain. We recently tested aluminum phosphate-adjuvanted whole-virion, monovalent prepandemic H5N1 and pandemic H1N1 influenza vaccines with only 6 g of HA and found them to be safe and immunogenic in pediatric, adult, and elderly subjects (8,(14)(15)(16)(17)(18). We also found that doses of 3.5 g did not trigger sufficient immune responses, while doses of 12 g were not substantially more immunogenic than 6-g doses when using monovalent vaccines (15).…”
mentioning
confidence: 99%
“…While the discrepency between a single dose or two doses for inducing a sufficient immune response in infants and children is yet to be elucidated, the recommendation has been for two doses in children. 86 Clinical trails in the elderly (>60 years) 80,85,87,88 and the very elderly (>75 years) 88 demonstrated that, as for young adults, a single dose of as little as 7.5 µg was safe and effective. The finding that an unadjuvanted single dose induces a sufficient level of immune response may be due to the presence of pre-existing cross-reactive antibodies 89 to H1N1 2009 that increase in prevalence with age [at baseline 29% of young adults (18-64 years), 44% for 65-74 year old and 63% at >75 years 88 ].…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%